As preposições no par de línguas português/espanhol: proposta de verbete bilíngue contrativo - CAROLINE EMANUELE DE OLIVEIRA BORSALLI (2024)
In this research, we present a proposal for a bilingual contrastive preposition entry in the Portuguese/Spanish language pair. The need for this research is justified by the absence of materials of this type in both Portuguese and Spanish, as special preposition dictionaries are based on verbal or nominal governance rather than taking the preposition itself as the headword. Considering the information that can be recorded in all parts that comprise the hyperstructure of a dictionary, our analysis is guided by the following questions: i) how are prepositions recorded in the lexicographic repertoires chosen for analysis? ii) is there coherence between the information in the front matter and the records in the word list (macrostructure) of these works? iii) in the case of bilingual dictionaries, besides equivalence, are there usage examples, records in the middle matter, or even contrastive information in both languages? Based on these questions, the following hypothesis was formulated: bilingual Portuguese/Spanish and Spanish/Portuguese dictionaries, as well as preposition dictionaries, do not include contrastive information on the uses of prepositions in this language pair. Thus, our general objective is to develop a prototype of a bilingual contrastive preposition entry, taking the preposition as the headword and targeting Brazilian learners of Spanish as a foreign language (ELE) at the basic and intermediate levels. Our specific objectives are: i) to discuss the development of communicative competence, focusing on lexical-grammatical competence; ii) to present the theoretical and methodological principles of Pedagogical Lexicography, Bilingual Lexicography, and Contrastive Bilingual Lexicography that underpin our lexicographic proposal; iii) to examine how prepositions are treated in bilingual Spanish/Portuguese and Portuguese/Spanish dictionaries, as well as in monolingual pedagogical and general dictionaries of the Spanish and Portuguese languages, and in special preposition dictionaries of the Spanish language, in order to highlight strengths and weaknesses related to the lexicographic recording of these language units; and iv) to identify, through the analysis of the lexicographic treatment of prepositions in bilingual, monolingual, and preposition dictionaries, models that can serve as guidance for the development of the desired entry prototype in this thesis. The research was conducted based on the theoretical and methodological principles of Pedagogical Lexicography, Bilingual Lexicography, Contrastive Bilingual Lexicography, and those related to Applied Linguistics in Language Teaching. To address the posed questions and meet the stated objectives, we analyzed seven bilingual dictionaries in both directions, Spanish/Portuguese and Portuguese/Spanish, four monolingual pedagogical dictionaries, four monolingual general dictionaries, and two preposition dictionaries exclusively in Spanish.In light of the study, we point out that most of the analyzed works do not include information on prepositions in the front matter or back matter, only in the word list, and that many of the analyzed entries offer only preposition equivalence without usage examples or contrastive information. Furthermore, we found that preposition dictionaries are based on the verb, noun, adjective, or adverb as the headword. Based on these findings, we hope that the results of this research contribute to metalexicographic studies being carried out in different academic contexts and, consequently, serve as a basis for the development and/or reorganization of lexicographic repertoires aimed at learners of Spanish as a foreign language. Keywords: Contrastive Bilingual Preposition Entry; Pedagogical Lexicography; Contrastive Bilingual Lexicography; Lexico-Grammatical Competence.